Photoelectrochemical behavior of AlxIn1−xN thin films grown by plasma-assisted dual source reactive evaporation - Alizadeh, M.; Ganesh, V.; Pandikumar, A.; Goh, B.T.; Azianty, S.; Huang, N.M.; Rahman, S.A. (Elsevier, 2016)
In this work the dependence of photoelectrochemical (PEC) behavior of AlxIn1−xN (0.48 ≤x ≤ 0.66) thin films grown by plasma-assisted dual source reactive evaporation, on the plasma dynamics and the alloys properties was studied. The influence of nitrogen flow rate on the compositional, morphological, structural and optical properties of the as-prepared films were investigated using X-ray photoelectron spectroscopy (XPS), Field emission scanning electron microscopy (FESEM), micro Raman spectroscopy and UV–vis spectroscopy. The PEC study of the as-grown AlxIn1−xN thin films targeted for water splitting application were performed in the presence of simulated solar irradiation of AM 1.5G (100 mW/cm2). The PEC results revealed that the photocurrent for the AlxIn1−xN thin film grown at nitrogen flow rate of 80 sccm is ∼10-fold higher than the dark current. From the Mott–Schottky (MS) plots it was deduced that by increasing N2flow rate up to 80 sccm, the flat band potential shifts toward more negative values. The good photoelectrochemical behavior of AlxIn1−xN thin films showed that this material could be a potential candidate for PEC water splitting.